The Influence of Financial Knowledge and Lifestyle of Hedonism on Financial Management Behavior Through Locus of control as A Moderation Variable - Andreapuspa, Serli; Muhdiyanto, M (Prosiding University Research Colloquium, 2022)
The success of financial management behavior in each individual can be measured by the factors that influence it. This study aims to examine and analyze the effect of financial knowledge and hedonistic lifestyle on financial management behavior through locus of control as a moderating variable on students at the University of Muhammadiyah Magelang, Faculty of Economics and Business. using purposive sampling method. The analytical tool used is Moderated Regression Analysis (MRA) with the help of the SPSS program. Based on the results of the research tests conducted, it shows that Financial Knowledge has a positive effect on Financial Management Behavior, Hedonic Lifestyle has no effect on Financial Management Behavior, Locus of control weakens the influence of Financial Knowledge on Financial Management Behavior and Locus of control does not moderate the Effect of Hedonistic Lifestyle on Behavior Financial Management.